EFFECT OF DIFFERENT MICRONUTRIENT GRADES ON POTATO PRODUCTION - Sasani, G. V.; Patel, C K.; Patel, R. N; Patel, N. H.; Patel, K P.; Patel, B. T (Potato Journal, 2013)
An experiment was conducted at Deesa during 2000 to 2002 in rabi season, growing potato cv. Kufri Badshah in light soils (Inceptisol) having marginal status of DTPA-Fe (5.84 ppm) and DTPA-Zn (0.86 ppm). The seve treatments comprising of four foliar multi-micronutrients formulations, two soil application grades and one control were tried in RBD with four replications. Potato tuber yield increased significantly due to foliar and soil application of micronutrients. One per cent foliar application of micronutrient grade (6 % Fe, 1 % Mn, 4 % Zn, 0.3 % Cu and 0.5 % B equivalent to Government notified Grade-II) at 40, 50 and 60 days after planting produced significantly highest tuber yield (444 q/ha) and net return. The effect of treatment was further confirmed by the uptake of the corresponding micronutrients. The yield improvement was mainly attributed to the quick correction of micronutrients deficiencies especially of Fe and Zn through foliar application. The overall results indicated that the supplementation of micronutrients in balanced proportion has beneficial effect in increasing the potato yields on soils which are marginal to deficient in micronutrients supply to the crop.